2019
DOI: 10.3390/cancers11121897
|View full text |Cite
|
Sign up to set email alerts
|

FOXD1 and Gal-3 Form a Positive Regulatory Loop to Regulate Lung Cancer Aggressiveness

Abstract: Dysregulation of forkhead box D1 (FOXD1) is known to promote tumor progression; however, its molecular mechanism of action is unclear. Based on microarray analysis, we identified galectin-3/LGALS3 (Gal-3) as a potential downstream target of FOXD1, as FOXD1 transactivated Gal-3 by interacting with the Gal-3 promoter to upregulate Gal-3 in FOXD1-overexpressing CL1-0 lung cancer cells. Ectopic expression of FOXD1 increased the expression of Gal-3 and the growth and motility of lung cancer cells, whereas depletion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 37 publications
1
25
0
Order By: Relevance
“…FOXD1 is also a determinant for the self‐renewal and tumorigenicity of mesenchymal glioma stem cells by combined with ALDH1A3 25 . In particular, pharmacological inhibition or gene knockout of FOXD1 significantly inhibited tumor cell proliferation, invasion and metastasis, stem cell maintenance, and promoting apoptosis both in vitro and in vivo 24‐26 . In summary, FOXD1 can serve as a potential biomarker and a valuable and predictable therapeutic target.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…FOXD1 is also a determinant for the self‐renewal and tumorigenicity of mesenchymal glioma stem cells by combined with ALDH1A3 25 . In particular, pharmacological inhibition or gene knockout of FOXD1 significantly inhibited tumor cell proliferation, invasion and metastasis, stem cell maintenance, and promoting apoptosis both in vitro and in vivo 24‐26 . In summary, FOXD1 can serve as a potential biomarker and a valuable and predictable therapeutic target.…”
Section: Discussionmentioning
confidence: 94%
“…From molecular level, it has demonstrated that FOXD1 regulates lung cancer aggressiveness by forming a positive feedback loop with Gal3 23 and influences aggressiveness and metastasis via indirect regulation of MMP9 and RAC1B alternative splicing in melanoma cells 21 . FOXD1 is also a determinant for the self‐renewal and tumorigenicity of mesenchymal glioma stem cells by combined with ALDH1A3 25 . In particular, pharmacological inhibition or gene knockout of FOXD1 significantly inhibited tumor cell proliferation, invasion and metastasis, stem cell maintenance, and promoting apoptosis both in vitro and in vivo 24‐26 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports indicated that FOXD1 plays a oncogenic effect in several types of cancer [ 30 , 31 , 32 , 33 , 34 , 35 , 36 ] and likely associates with the mechanism for radioresistance [ 37 ]. In this study, our data showed that FOXD1 is capable of directly regulating the expression of G3BP2 , which is capable of inhibiting p53 activity through a direct binding, which may further promote p53 nuclear export via increasing p53 sumoylation [ 38 ] and serves as a poor prognostic marker in prostate cancer patients [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Present study identified FOXD1 as a target of miR-429. FOXD1, located at chromosome 5q12, is a newly discovered member of the FOX transcription factor family [ 43 ] and acts as a tumor facilitator in various cancers [ 33 , 44 , 45 ]. Currently, we discovered that FOXD1 interacted with miR-429 and was positively regulated by OIP5-AS1.…”
Section: Discussionmentioning
confidence: 99%